TINGKAT SERANGAN RAYAP PADA GEDUNG SEKOLAH DI KOTA PONTIANAK - dika, An; Indrayani, Yuliati; Yanti, Hikma (JURNAL HUTAN LESTARI, 2013)
The research was conducted in Pontianak with 44 samples of school distribute in six districts in Pontianak City. Research using descriptive method by field survey. The results of the survey on 44 buildings located in six districts in Pontianak city, indicate that percentage of termites attack as follows : underpinnings is 26.28%, girder is 45.5%, column / pillar structure is 62.35%, table is 89.01%, chair is 90.44%, doors is 33.88%, ceiling framework is 36.01%, 64.53% and rafters is 47.9%. The Relative frequencies (FK) of termites attack as follows: Nasutitermes havilandi (59.09%), Cryptotermes sp (20.45%), Cryptotermes sp1 (4.54%), Cryptotermes domesticus (18.18%) , C. cynocephalus (9.09%), Coptotermes curvignathus (18.18%), Coptotermes kalshoveni (2.27%), Schedorhinotermes medioobscurus (9.09%), Globitermes globosus (2.27%) and Microcerotermes havilandi (2.27%). Key word : Level of termite attack, School building, Pontianak city